Analytical methods for assessing paper degradation In transformers - Christofidis, Stavros (Cranfield University, 2006)
Power transformers are essential equipments for distributing electricity. However, maintenance of these equipments is necessary to ensure long working life and to avoid catastrophic incidents. Insulation of the instrument is essential, and mainly consists of mineral oil and cellulosic paper. This research work investigates and examines in a series of different experiments the compounds produced from the degradation of the cellulosic paper, known as furanic compounds. Five furanic derivatives (5-HMF, 2-FAL, 2-ACF, 5-MEF and FOL) were examined, and it was established throughout this work that these furanic compounds degradate faster in aqueous solution, under a controlled environment, than in an organic, it is possible to produce from one furanic compound other derivatives, and finally each furanic compound distributes differently in an oil water environment, affecting the recovery of each individual. The knowledge obtained from this research work can be used for the development of the existing method of analysis of furanic compounds, and help to provide a better diagnosis of the insulation state of the transformer.